The Effects of Hand-Eye Coordination on Basketball Passing at PublicSenior High School 1 Lasem - Sufyandi, Ardianto; Sulaiman, Sulaiman; Soegiyanto, Soegiyanto (Journal of Physical Education and Sports, 2019)
This study aimed to determine the skill ability of male students of basketball senior extracurricular at Public Senior High School 1 Lasem, through a training model used in passing the basketball and hand-eye coordination. This research is experimental research using a 2x2 factorial or design method. The population of the study was students of the Extracurricular Basketball, Public Senior High School 1 Lasem. Thesample is 20 students. This study is using ANOVA. The variables studied were the independent variable the level of high hand-eye coordination and the level of low hand-eye coordination. Independent variables manipulated are wall toss back and triangle pass training model. The results showed that overall passing skills in the group of students treated with triangle pass training method were better than the group of students who were treated with woll toss back training method. Based on the conclusions of the study results and the implications described above, suggestions are suggested as follows: physical education teachers, trainers, and sports coaches to develop learning methods that refer to the training method of passing skills, in addition to the training method must also consider hand-eye coordination.